2020
DOI: 10.2196/18959
|View full text |Cite
|
Sign up to set email alerts
|

Decision Support Capabilities of Telemedicine in Emergency Prehospital Care: Systematic Review

Abstract: Background Telemedicine offers a unique opportunity to improve coordination and administration for urgent patient care remotely. In an emergency setting, it has been used to support first responders by providing telephone or video consultation with specialists at hospitals and through the exchange of prehospital patient information. This technological solution is evolving rapidly, yet there is a concern that it is being implemented without a demonstrated clinical need and effectiveness as well as w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Although information acquisition and processing are quite difficult in prehospital areas, various instruments and information systems could attribute to diminish those problems. Complex data acquisition like mobile CT or other unstructured data, 41 information sharing through telemedicine 42 and decision support tools in prehospital environments 43 could contribute to the accurate assessment of EMS providers. More information acquisition and real-time processing of those data could improve the clinical prediction models in prehospital areas, which could lead to the improvement of patients’ safety and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although information acquisition and processing are quite difficult in prehospital areas, various instruments and information systems could attribute to diminish those problems. Complex data acquisition like mobile CT or other unstructured data, 41 information sharing through telemedicine 42 and decision support tools in prehospital environments 43 could contribute to the accurate assessment of EMS providers. More information acquisition and real-time processing of those data could improve the clinical prediction models in prehospital areas, which could lead to the improvement of patients’ safety and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…31 In patients with stroke, myocardial infarction, septicemia, or pneumonia, time to effective therapy is a major determinant of prognosis. 32 Kim et al 29 found that remote expert consultation helped make accurate pre-hospital diagnoses using vital signs and image transfers. Vital signs are indicators of certain diseases such as infection, respiratory problems, and heart diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we have considered studies evaluated in research settings and published exclusively in research journals. The final searches were based on the Embase search strategy ( Table S1 ), and searches were adapted as appropriate to the specifications of the databases [ 40 ].…”
Section: Methodsmentioning
confidence: 99%